5-2(T+4)=(3T+12)

Simple and best practice solution for 5-2(T+4)=(3T+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2(T+4)=(3T+12) equation:


Simplifying
5 + -2(T + 4) = (3T + 12)

Reorder the terms:
5 + -2(4 + T) = (3T + 12)
5 + (4 * -2 + T * -2) = (3T + 12)
5 + (-8 + -2T) = (3T + 12)

Combine like terms: 5 + -8 = -3
-3 + -2T = (3T + 12)

Reorder the terms:
-3 + -2T = (12 + 3T)

Remove parenthesis around (12 + 3T)
-3 + -2T = 12 + 3T

Solving
-3 + -2T = 12 + 3T

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Add '-3T' to each side of the equation.
-3 + -2T + -3T = 12 + 3T + -3T

Combine like terms: -2T + -3T = -5T
-3 + -5T = 12 + 3T + -3T

Combine like terms: 3T + -3T = 0
-3 + -5T = 12 + 0
-3 + -5T = 12

Add '3' to each side of the equation.
-3 + 3 + -5T = 12 + 3

Combine like terms: -3 + 3 = 0
0 + -5T = 12 + 3
-5T = 12 + 3

Combine like terms: 12 + 3 = 15
-5T = 15

Divide each side by '-5'.
T = -3

Simplifying
T = -3

See similar equations:

| X+6=-40 | | Ln(x+12)=8 | | 972=x(3x) | | 7x+8y+(-8y)+(-9x)= | | 1/4=y=12 | | 40x^2+116x+84= | | -8n^2-12n+14=8 | | -x-178=5x+176 | | 700=29*24 | | -27.6=18.1+m | | X^2-17=17 | | 2k^2=49+7k | | -9=-m | | -27.6=18.1m | | -n^2-15n+72=-9n | | 130+2x=9x-129 | | 5x+20forx=1.5 | | X^2-20=-3 | | -6+3k-4K+7= | | 4(2x-3)(3x-4)= | | (Y-5)3=20 | | 16x-8-8x=24 | | 30x^2-40x-40= | | 5(x+2)=-2(1-4x)-6x | | X^2-7=103 | | (7-8i)+(-12-4i)=0 | | 3n+2=122 | | -72ac+36xy=0 | | 22=18-n/5 | | 2pq^2+4pq-2q-4=0 | | 3+6+6r+2r=1 | | 3(-6p-6)=-144 |

Equations solver categories